Asuhan keperawatan pada Ny.N dengan diabetes melitus tipe II di ruang pejuang RSUD Bangkinang Tahun 2025 - Safitri, Wiwit; Hidayat, Ridha (Jurnal Spektrum Kesehatan Indonesia, 2025)
Diabetes mellitus is a chronic non-communicable disorder characterized by increased blood sugar levels (hyperglycemia) and metabolic conditions that can cause blood glucose levels to be higher than normal. Signs and symptoms of diabetes mellitus include polyuria, polydipsia, polyphagia, blurred vision, numbness in the hands and feet. The purpose of this study is to examine and implement nursing care for patients with type II diabetes mellitus in the fighter room of RSUD Bangkinang in 2025. This research method uses a descriptive research design in the form of a case study. Subjective in the case report is Mrs. N, 50 years old with type II diabetes mellitus in the Fighter room of RSUD Bangkinang which was carried out for 3 days from 16 to 18 May 2025. Data obtained through interviews, physical examination and supporting examinations. During the assessment, the client felt weak, nauseous, vomiting, headache, and frequent urination. The researcher formulated the main problem with the nursing diagnosis of unstable blood glucose related to hyperglycemia (D.0027). The intervention given was to monitor blood glucose levels. In the implementation of nursing actions for Mrs. N with type II diabetes mellitus, it was carried out according to the nursing plan that had been prepared. The results of nursing visits for three days on the client, the problem was resolved. Nursing evaluation for three days on this client is a guideline for researchers as a goal to conduct research on Diabetes Mellitus, campus as a reference in providing nursing care for patients.